MTHFR rs1801133 polymorphism and susceptibility to colorectal cancer in Iranian population: evidence of a case–control study and meta-analysis. (November 2016) - Haerian, Monir Sadat; Haerian, Batoul Sadat; Molanaei, Saadat; Kosari, Farid; Sabeti, Shahram; Bidari-Zerehpoosh, Farahnaz; Abdolali, Ebrahim; Zali, Mohammad Reza
Several studies have investigated whether MTHFR rs1801133 polymorphism contributes to risk of colorectal cancer (CRC), however the results are inconclusive.Aim: The purpose of this study was to investigate this hypothesis in a case–control study and meta-analysis in Iranian population.Materials & methods: This polymorphism was genotyped in the 2421 subjects (46% CRC patients) from Tehran. Meta-analysis was performed for determining the risk effect size of this polymorphism on CRC.Results: Both case–control study and meta-analysis showed no association between rs1801133 and CRC risk or its features.Conclusion: This study failed to identify an association between the rs1801133 and susceptibility to CRC in Iranian population.